2018
DOI: 10.1155/2018/8514619
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC‐Q‐TOF MS‐Based Metabolic Analysis for the Therapeutic Efficacy of “Xuebijing Injection” against Sepsis‐Induced Acute Lung Injury

Abstract: “Xuebijing Injection” (XBJ) is a traditional Chinese medicine and has been wildly used in the treatment of sepsis in China. However, few studies have reported the use of XBJ in sepsis with acute lung injury (ALI). This study aimed to investigate the therapeutic efficacy of XBJ against sepsis-induced ALI. Generally a total of 27 mice were equally randomized into three groups: a sham group was given saline before sham operation. A sepsis group received the cecal ligation and puncture (CLP) operation only. A seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
6
2
Order By: Relevance
“…The changes of lysoPC can evaluate the effect of treatment and help in the prediction of mortality in ICU patients with sepsis. On the other hand, in septic patients, sphingolipid is similar to other lipids, showing a trend of substantial decline. This trend can be reversed after treatment . However, in this study, sphinganine increased in the sepsis group.…”
Section: Discussioncontrasting
confidence: 62%
“…The changes of lysoPC can evaluate the effect of treatment and help in the prediction of mortality in ICU patients with sepsis. On the other hand, in septic patients, sphingolipid is similar to other lipids, showing a trend of substantial decline. This trend can be reversed after treatment . However, in this study, sphinganine increased in the sepsis group.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous studies have shown that XFZYD can significantly improve lung injury induced by sepsis and LPS [ 20 ]. XFZYD can reduce endothelial dysfunction and maintain endothelial function homeostasis by inhibiting ROS-induced oxidative stress, thereby inhibiting the inflammatory response and reducing apoptosis [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lan et al. found that salidroside can reduce the content of some pro-inflammatory factors, such as tumor necrosis factor-α (TNF-α), nitric oxide (NO) and interleukin-6 (IL-6), in mice with ALI [ 9 ]. Shi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) research has become increasingly popular [6,7,8], and studies have shown that a variety of natural compounds extracted from such plants can effectively regulate ALI. For example, Lan et al found that salidroside can reduce the content of some pro-inflammatory factors, such as tumor necrosis factor-α (TNF-α), nitric oxide (NO) and interleukin-6 (IL-6), in mice with ALI [9]. Shi et al demonstrated that injections composed of rutin, chlorogenic acid, and ferulic acid can regulate ALI by participating in the metabolism of fatty acids, amino acids, and purines in mice with ALI [10].…”
Section: Introductionmentioning
confidence: 99%